The "Flat Earth" Belief: The Scientific Evidence of its Inconsistency. A Narrative Review - Perrotta, Giulio; Sellari, Arianna (Archives of Community Medicine and Public Health, 2025)
The belief in a "flat Earth" has ancient roots and remained unchanged for several millennia, albeit with some differences in popular narrative tradition. With the flourishing of the scientific method in the fifteenth and sixteenth centuries AD, this belief increasingly lost ground, being labeled exclusively as a popular belief. Few articles in the scientific literature address this topic, and all equally confirm this conclusion. However, even today, starting in the twentieth century, thousands of people have returned to disbelief in anti-scientific theories, which underline conspiracy and religious sectarian movements and groups, consistent with subversive critical thinking. This narrative review analyzes the main tenets of this "false" belief and the scientific positions that refute it, to conclusively demonstrate its scientific and technical inconsistency.